PENGARUH KOMPENSASI, HUBUNGAN INTERPERSONAL, KESEMPATAN BERPRESTASI DAN KONDISI KERJA TERHADAP KEPUASAN KERJA KARYAWAN RUMAH SAKIT UMUM DAERAH BANGIL - Liemgiani, Liemgiani (Manajemen & Bisnis Jurnal, 2018)
In fact, the effectiveness and productivity of an organization is greatly affected by job satisfaction. Conversely, job dissatisfaction will cause a decrease in enthusiasm and enthusiasm for work. The number of cases of work strikes lately, irrespective of the motives of each individual, implies employee dissatisfaction with the organization. This is certainly very disturbing the effectiveness of the company as a form of organization. One program that needs to be considered in the context of optimizing human resources is to meet job satisfaction. With the fulfillment of job satisfaction, individual employees will try to improve their abilities. The success or failure of an organization depends on the ability of the organization to provide job satisfaction to its employees. The purpose of this study (1) To determine the simultaneous influence of compensation variables, interpersonal relationships, opportunities for achievement, and work conditions affect employee job satisfaction at the Bangil District General Hospital. (2) To determine the partial effect of compensation variables, interpersonal relations, opportunities for achievement, and work conditions affect employee job satisfaction at the Bangil District General Hospital. The results showed that simultaneous compensation variables, interpersonal relationships, achievement opportunities and working conditions have a significant influence on employee job satisfaction in Bangil District General Hospital, while partially the compensation variables, interpersonal relationships and working conditions have an influence on employee job satisfaction at General Hospitals Bangil area. Keywords: Compensation, Interpersonal Relationships, opportunities for achievement, working conditions and job satisfaction